2014
DOI: 10.1007/s13197-014-1276-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant tertiary butyl hydroquinone on the thermal and oxidative stability of sesame oil (sesamum indicum) by ultrasonic studies

Abstract: The aim of the current investigation is to evaluate the efficiency of tertiary butyl hydroquinone (TBHQ) as an antioxidant in sesame oil (sesamum indicum) by density, viscosity and ultrasonic velocity. The effects of varying amounts of TBHQ on the oxidation stability of sesame oil have been investigated. The antioxidant incorporated sesame oil system and control edible oil were subjected to heating at 180 ± 5 °C continuously for a period of 4 h per day for consecutive 4 days. The parameters used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…In the 5th cycle, the addition of Nanox 189 showed the lowest viscosity, with about 73.2 cP, which increased to 80.3 cP at the 30 th frying cycle. This is correlated with Prasad et al [37], who stated that oil containing 200 ppm TBHQ changed the viscosity to a small extent during the frying process. The highest level of TBHQ mixed oil exhibits the lowest change in oil viscosity.…”
Section: Viscositysupporting
confidence: 83%
“…In the 5th cycle, the addition of Nanox 189 showed the lowest viscosity, with about 73.2 cP, which increased to 80.3 cP at the 30 th frying cycle. This is correlated with Prasad et al [37], who stated that oil containing 200 ppm TBHQ changed the viscosity to a small extent during the frying process. The highest level of TBHQ mixed oil exhibits the lowest change in oil viscosity.…”
Section: Viscositysupporting
confidence: 83%
“…11 Sesamol (3,4-methylenedioxyphenol) is a main constituent of sesame seed oil and is obtained from Sesamum indicum. [12][13][14] Sesamol also has antioxidant, antimicrobial, chemoprevention, and antimutagenic properties. [15][16][17] In experimental studies, sesamol is shown to have promising beneficial effects against hepatotoxicity, pancreatitis, heart diseases, diabetes, and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that TBHQ was found in the samples analyzed, while BHA and BHT were not found. TBHQ is odorless and stable at high temperature especially for the frying oils, therefore the edible oil manufacturers desire to use only TBHQ as the antioxidant agent . The samples were diluted by the blank oil to put the concentration inside the dynamic range.…”
Section: Resultsmentioning
confidence: 99%